Effect of lattice defects on shape memory properties of Fe-Mn-Si alloys - Druker, Ana Velia (2010)
We have investigated two shape memory ferrous alloys, Fe-30Mn-4Si and Fe-15Mn-4Si-9Cr-5Ni, processed by different thermo-mechanical ways, in order to analyze the effect of processing conditions and the stacking fault energy values on their shape memory properties. Rolling was conducted at 20, 600-800 and 1000ºC, and afterwards the sheets were annealed between 650 and 1000ºC. The density and structure of dislocations, as well as the presence of stacking faults, strongly depend on the process temperatures. Among the investigated cases, the alloy containing 15% Mn, rolled at 800°C and annealed at 650°C, the recovery temperature, shows the best shape memory behavior.